La deuda y su incidencia en la rentabilidad de las pymes de Boyacá, (Colombia) (2018)
This article seeks to analyze the incidence of debt on the profitability of pyramids in the department of Boyacá, Colombia, for which, several hypotheses have been raised taking as elements: the size of the company, the asset or fixed asset, the cost of capital, and sales, aspects that are proven through financial ratios and theoretically contrasted with the contributions of Modigliani and Miller, the theory of trade off or static equilibrium, the theory of Myers and Majluf, among others. Among the main results found in the investigation, it could be established that the levels of debt assumed by the organizations are related to the size of the company, profitability, cost of capital, fixed assets and constitute a low patrimonial risk. It also establishes that the typology of small businesses in the region is associated with financing problems, which are inherent to active or reactive pyramids, that is, small organizations with low levels of profitability that survive with short-term decisions.